STUDENTS’ PERCEPTION AND PROBLEMS IN LEARNING ENGLISH USING GOOGLE CLASSROOM DURING THE COVID-19 PANDEMIC - DIANA, NOVA; YUNITA, WISMA; HARAHAP, ALAMSYAH (Linguists : Journal of Linguistics and Language Teaching, 2021)
The Covid-19 pandemic has occurred across the world. This causes all segments of human life to be disturbed including the education sector. The teaching and learning process tends to run ineffectively and should be done online. Online learning offers a learning process that can be done not only in the classroom but anywhere and anytime. One of the applications that can be used is Google classroom. This study aims to determine students' perceptions and problems in learning English using Google Classroom during the Covid-19 Pandemic at SMAN 6 Kota Bengkulu. This research was a mixed-method research involving 443 students in the academic year of 2020/2021. The data were collected using a questionnaire in the form of a Google form consisting of 50 questions with 4 answer choices, namely strongly agree, agree, disagree, and strongly disagree, and semi-structured interviews. The data obtained were analyzed quantitatively and qualitatively. The results of this research indicate that the students have a positive perception in learning English using Google classrooms during the Covid-19 pandemic at SMAN 6 Kota Bengkulu with the average score obtained was 1160 and was in the positive category. Moreover, the data obtained from the interview showed that most of the students experienced problems in learning English skills using Google classroom caused by lack of vocabulary. In addition, the problems in using the Google classroom application were in the opening and uploading files or videos. These findings are expected that the teachers should change their teaching habits by offering students innovative opportunities to improve their self-confidence, to control their learning, and to practice their language skills. The students should be more creative to solve the problems during learning English by using Google classroom even in the online process or not.